Secure login technique for online banking - Yaseen Khudhur, Doaa; Al-Khateeb, Belal; Amjed Saeed, Hadeel (International Journal of Engineering and Technology, 2019)
In recent years, there are many authentication protocols that are used in the accessing of the sensitive and private data. However most of those methods have many weaknesses by which data can be extracted and used by unauthorized people this due to the use of a one level authentication that may face many attacks. This paper presents an authentication method that involves three levels of user authentication; the first two levels use two level passwords authentication together with a Personal Identification Number (third level) for every operation in Electronic Banking system. Hash functions -Secure Hash Algorithms- and Cyclic Redundancy check (32) for the generations of Personal Identification Number are used. This system eliminates the problem that is related with single level password authentication system and improves the security by using Personal Identification Number.Â